Interstitial brachytherapy combined with PARP inhibitors in the treatment of chemoresistant recurrent epithelial ovarian cancer: A case report - Bian, Yuan; Guan, Ping; Li, Dan; Tan, Longjing; Pang, Haowen; Wen, Qinglian; Chen, Ping; Zhang, Zhenhua (Frontiers in Oncology, 2022)
Background: Chemoresistance generally develops in patients with advanced epithelial ovarian cancer, and the prognosis is still very poor, with an expected survival time of less than one year. For this population of individuals, there is currently no standard protocol for clinical benefit. Case Presentation: We report a case of an elderly woman diagnosed with stage IIIC high-grade serous ovarian cancer (HGSOC). During a follow-up time of 6 years, the patient initially received multiple sequential courses of chemotherapy with platinum-based regimens and with no maintenance therapy. Similar to most patients with advanced HGSOC, she developed platinum resistance and experienced poor treatment results with a short progression-free survival (PFS). Ultimately, we gave the patient traditional non-platinum-based chemotherapy with bevacizumab and high-dose-rate interstitial brachytherapy followed by olaparib as a maintenance therapy. Up to now, the patient did response well to the treatment, and the PFS had exceeded 12 months. Conclusion: High-dose-rate interstitial brachytherapy combination with PARP inhibitors may be an option for isolated chemoresistant recurrent epithelial ovarian cancer.